The new donor vigilance system in Denmark reveals regional differences in adverse reactions supposedly caused by variation in the registration. Issue 3 (15th September 2021) - Mikkelsen, Christina; Paarup, Helene Martina; Bruun, Mie Topholm; Pedersen, Louise Ørnskov; Hasslund, Sys; Larsen, Rune; Aagaard, Bitten; Sørensen, Betina Samuelsen
Abstract: Background and Objectives: In recent years, there has been an increased focus among blood bank professionals on the health and safety of blood donors. In 2019, the Danish Haemovigilance Committee designed a national donor vigilance system to improve the registration of adverse reactions (AR) in blood donors. The new donor vigilance system was implemented on 1 January 2020 and we here present the results from the first year of registration. Materials and Methods: AR categories, severity level and imputability score were defined based on the definitions from the International Society of Blood Transfusion, AABB and the European Commission directive 2005/61/EC, respectively. Results: Across all severity levels, AR in Danish blood donors were found to be rare (1498 per 100, 000 donations). Only 0.2% of the registered reactions were classified as serious (2.7 per 100, 000 donations). Large regional differences were seen in the registration of citrate reactions and haematomas. Conclusion: Significant differences across regions in what to categorize as an AR were persistent even when including a severity score in the reporting. The Danish Haemovigilance Committee will commence a national work to align the definitions but suggests that this matter is raised to an international level as part of the current work to agree upon definitions for assessment of donor AR.